Genetic toxicology - Bunch, Roderick Todd (Henry Stewart Talks, 2009)
Mutagenicity testing, Clastogenicity testing, Additional assays, Regulatory genetic toxicology, Current regulations, In vitro mutagenicity and clastogenicity, In silico, Integration of results and data interpretation, Genotoxic impurity testing